Spatial analysis of underfill flow in flip-chip encapsulation - Ng F.C.; Zawawi M.H.; Abas M.A. (Emerald Group Holdings Ltd., 2023)
Air; Filling; Flip chip devices; Flow patterns; Soldering; Design/methodology/approach; Flip-chip encapsulation; Package designers; Process enhancements; Research studies; Spatial analysis; Unit cell approach; Visualization tools; Spatial variables measurement